2012
DOI: 10.1038/leu.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

How to manage children and young adults with myeloproliferative neoplasms

Abstract: On the basis of my personal clinical and research experience and validated by the current literature, my approach to the management of pediatric (age o18 years) and young patients (age o40 years) with classic myeloproliferative neoplasms is presented by focusing on diagnosis, patient communication, risk stratification and therapy. The WHO-2008 diagnostic criteria are recommended, even though in children suspected with essential thrombocythemia (ET), a specific set of diagnostic features may be required. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 60 publications
1
47
0
2
Order By: Relevance
“…One report recommends aspirin in young adult patients with erythromelalgia or cardiovascular risk factors. 85 In addition, one study in adults suggested that aspirin should be given twice daily in these patients because of enhanced platelet turnover. …”
mentioning
confidence: 99%
See 3 more Smart Citations
“…One report recommends aspirin in young adult patients with erythromelalgia or cardiovascular risk factors. 85 In addition, one study in adults suggested that aspirin should be given twice daily in these patients because of enhanced platelet turnover. …”
mentioning
confidence: 99%
“…85 In addition, one study in adults suggested that aspirin should be given twice daily in these patients because of enhanced platelet turnover.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…La TE con frecuencia se observa entre los 65 a 70 años, con un rango de edad variable, es poco frecuente en menores de 30 años y se presenta predominante en el sexo femenino (1,6,7).…”
Section: Introduccionunclassified